Viewpoints to labour mobility development - András Kalmár (Journal of Contemporary Economic and Business Issues, 2015)
The goal of the paper is to provide viewpoints to labour mobility development in the Western Balkans and in Macedonia in particular, since it would be one of the advantages of joining the European Union. The EU integration process of the Western Balkans opens up new dimensions for labour mobility in the long run in two aspects. One is the possibility of revitalization of the earlier notion of 'intra mobility' of Yugoslavia, especially since there are small language barriers among the successor countries. Once the candidate countries become part of the Community, these new borders will naturally be brought down once again. The broader possibility and a special added value of joining the European Union would be the free access to the labour market of EC countries. The landlocked country of Macedonia could be in a very advantageous position in the long run, being surrounded by practically either existing members of the EU, or candidate countries. It lies at the junction of important communication routes, and has a long history of migration. Europe's historically established migrations patterns - from the east towards the west and from the south to the north - suggest that the country, at least in the short and middle run, will benefit from the free mobility of workers. There have been development projects related to labour mobility. One has been carried out by the International Organization for Migration (IOM), establishing migration centres in Macedonia, as well as an EU Twinning project supporting capacity building regarding preparations for the free movement of workers. Mobility can offer employment possibilities and opportunities for a great number of jobseekers, and through transfer of capital and know-how, returning skilled labour force and business ties can boost the economy and the domestic labour market. There are however obstacles to the free movement, and national policies can have a great role in overcoming these difficulties, ranging from regional infrastructure policies to narrowing the information gaps by guidance networks up to targeted mobility schemes all aiming at mobility becoming a reality. Public Employment Services have a crucial role in facilitating of all relevant players in the field in order to create an environment where mobility becomes a natural phenomenon and disadvantages are reduced to a minimum. Based on the experiences of the EU countries, development of labour mobility provides a lot of advantages as regards raising of employment levels, and the growing competition for skilled workers calls for a systematic strategy. This paper aims to enlist the most typical barriers to mobility and take into account the latest trends and methods in mobility development. In order to overcome the barriers to mobility (classified herein as information, financial and administrative gaps), Public Employment Services should at best develop their Lifelong Guidance systems (including mobility questions), and complex financial solutions 'mobility schemes'.
Keywords: J60; J61; J62; J68; 330; labour mobility; barriers to mobility; employment possibilities